Reduction‐Driven 3D to 2D Transformation of Cu Nanoparticles. Issue 7 (12th January 2022) - Matte, Lívia P.; Thill, Alisson S.; Lobato, Francielli O.; Novôa, Matheus T.; Muniz, André R.; Poletto, Fernanda; Bernardi, Fabiano
Abstract: The interaction between metal and metal oxides at the nanoscale is of uttermost importance in several fields, thus its enhancement is highly desirable. In catalysis, the performance of the nanoparticles is dependent on a wide range of properties, including its shape that is commonly considered stable during the catalytic reaction. In this study, highly reducible CeO2‐ x nanoparticles are synthesized aiming to provide Cu/CeO2‐ x nanoparticles, which are classically active catalysts for the CO oxidation reaction. It is observed that the Cu nanoparticles shape changes during reduction treatment (prior to the CO oxidation reaction) from a nearly spherical 3D to a planar 2D shape, then enhances the Cu–CeO2‐ x interaction. The spread of the Cu nanoparticles over the CeO2‐ x surface during the reduction treatment occurs due to the minimization of the total system energy. The shape change is accompanied by migration of O atoms from CeO2 surface to the border of the Cu nanoparticles and the change from the Cu 0 to Cu +1 state. The spreading of the Cu nanoparticles influences on the reactivity results toward the CO oxidation reaction since it changes the local atomic order around Cu atoms. The results show a timely contribution for enhancing the interaction between metal and metal oxide. Abstract : Cu nanoparticles subjected to a reduction treatment in CO atmosphere at 400 °C undergo a structural transformation from a spherical 3D to a planar 2D shape. The wetting of the Cu nanoparticles over CeO2 surface influences on the local atomic order around Cu atoms and, consequently, on the reactivity toward the CO oxidation reaction.